2020
DOI: 10.1109/access.2020.2982261
|View full text |Cite
|
Sign up to set email alerts
|

Foreground Information Guidance for Siamese Visual Tracking

Abstract: Existing Siamese network based trackers are easily disturbed by large deformation, occlusion and distractor objects in the background. By comparing these trackers, we observe that the monotonous positive pairs usually have limited challenging factors (Occlusion, Deformation, etc.), which may make the learned features less robust. In addition, the foreground information of the substantial training data is utilized directly without deeper exploration. Thus, the trackers cannot effectively discriminate the foregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The logistic loss was adopted in trackers SiamFC [12], Correlation filter network (CFNet) [54] and Dynamic Siamese network (DSiam) [55]. This loss was a foundation to many upcoming trackers, e.g., Siamese classification and regression networks (SiamCAR) [20] or Foreground information guidance for Siamese visual tracking (FIGSiam) [56], where they extended this loss by adding more terms.…”
Section: ) Margin Contrastive Lossmentioning
confidence: 99%
See 4 more Smart Citations
“…The logistic loss was adopted in trackers SiamFC [12], Correlation filter network (CFNet) [54] and Dynamic Siamese network (DSiam) [55]. This loss was a foundation to many upcoming trackers, e.g., Siamese classification and regression networks (SiamCAR) [20] or Foreground information guidance for Siamese visual tracking (FIGSiam) [56], where they extended this loss by adding more terms.…”
Section: ) Margin Contrastive Lossmentioning
confidence: 99%
“…This analysis opened up the possibility to use a broader set of backbones, and successive works (e.g., [56]) also adopted the spatial-aware sampling strategy to counterbalance the breaking of strict translation invariance. An analysis by Han et al [67] also confirmed that using padding in Siamese backbones had a huge negative impact on tracking performance.…”
Section: A Backbone Selection and Pre-trainingmentioning
confidence: 99%
See 3 more Smart Citations